Respon Pertumbuhan dan Hasil Tanaman Seledri (Apium graveolens L.) Pada Perlakuan Beberapa Media Tanam dan Pupuk Organik Cair - Muhamad Yusuf; Muhammad Yusuf N (Faculty of Agriculture, Universitas Malikussaleh, 2017)
This research aims to determine the role of planting media and organic fertilizer to the growth and yield of celery plants. This research was conducted at Gampong Lancang Barat District Dewantara Regency of North Aceh, with height of place more about 5 m asl with flat condition (average) Implementation of research from March until June 2015. This study used Factorial Randomized Block Design. 2 Factors studied: Planting media factor (M), consisting of 4 levels: M0: soil (5 kg) M1: soil + manure (3:2) M2: soil + sand (3:2) M3: soil + ash husk (3:2). The organic liquid fertilizer (P) factor consists of 3 levels: P0: without fertilization P1: the application of liquid organic fertilizer as much as 2 cc / liter of water P2 the application of liquid organic fertilizer as much as 4 cc / liter of water. Thus there are 12 treatments in repeated three times, so that obtained 36 units of experiment. The results showed that planting media had significant effect on plant height, number of leaves, number of midrib, length of stem at 15, 30, 45 and 60 HST, leaf area, wet and dry weight. Growth and best results were found in soil media treatment with a mixture of husk ash (M3). Organic fertilizers have a very significant effect on plant height, number of leaves, number of midrib, length of stem at 15, 30, 45 and 60 HST, leaf area, wet and dry weight. Growth and best results are found in the application of liquid organic fertilizer as much as 4 cc / liter of water (P2). There is an interaction between plant media treatment and organic fertilizer application on plant height, leaf number, midrib, mid-length at age 15, 30, 45 and 60 HST, leaf area, wet and wet weighting. The best interaction is found in soil media treatment with a mixture of husk ash and liquid organic fertilizer as much as 4 cc / liter of water (M3P2).